2012
DOI: 10.1155/2012/962012
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Fasting Modulation of the Diabetic Syndrome in Streptozotocin-Injected Rats

Abstract: This study investigates the effects of intermittent overnight fasting in streptozotocin-induced diabetic rats (STZ rats). Over 30 days, groups of 5-6 control or STZ rats were allowed free food access, starved overnight, or exposed to a restricted food supply comparable to that ingested by the intermittently fasting animals. Intermittent fasting improved glucose tolerance, increased plasma insulin, and lowered Homeostatis Model Assessment index. Caloric restriction failed to cause such beneficial effects. The β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 25 publications
1
59
0
1
Order By: Relevance
“…Diabetic STZ rats were obtained as described elsewhere [8], GK rats were obtained from the Paris colony, initiated by the end of the 1980s [9] from the original Japanese colony [10] and maintained from that time at the University Paris-Diderot animal core [11]. Parotid and submaxillary glands, heart, kidney, liver, lung, soleus muscle and pancreas were removed and processed for quantitative real-time PCR analysis as previously described, according to the delta Ct method, the gene expression level of each mRNA being normalized to relative GAPDH (glyceraldehyde 3-phosphate dehydrogenase enzyme) mRNA [7].…”
Section: Methodsmentioning
confidence: 99%
“…Diabetic STZ rats were obtained as described elsewhere [8], GK rats were obtained from the Paris colony, initiated by the end of the 1980s [9] from the original Japanese colony [10] and maintained from that time at the University Paris-Diderot animal core [11]. Parotid and submaxillary glands, heart, kidney, liver, lung, soleus muscle and pancreas were removed and processed for quantitative real-time PCR analysis as previously described, according to the delta Ct method, the gene expression level of each mRNA being normalized to relative GAPDH (glyceraldehyde 3-phosphate dehydrogenase enzyme) mRNA [7].…”
Section: Methodsmentioning
confidence: 99%
“…When diabetic BDNF+/− mice are maintained on an ADF diet, their circulating levels of glucose, insulin and leptin are reduced, and glucose tolerance is normalized (Duan et al, 2003a). Interestingly, IF can ameliorate the insulin deficit and glucose intolerance in a rat model of type I diabetes by a mechanism involving preservation of pancreatic β-cells (Belkacemi et al, 2012). Although not yet established, it is likely that enhancement of cellular stress resistance by IF protects β-cells, as has been reported in studies of the effects of IF on other cell types (e.g., myocardial cells and neurons) (Mattson and Wan, 2005; Mattson, 2015).…”
Section: If and Health Indicators In Laboratory Animalsmentioning
confidence: 99%
“…The increased heart rate variability in rats maintained on ADF may result from enhanced activity of brainstem cholinergic cardiovagal neurons (Mager et al, 2006; Wan et al, 2014). Levels of circulating cholesterol and triglycerides are reduced in animals on ADF and TRF diets (Varady et al, 2007; Belkacemi et al, 2012; Chaix et al, 2014). TRF protects mice against obesity and metabolic syndrome caused by consumption of atherogenic diets including a high fat + glucose diet and a high fructose diet (Chaix et al, 2014).…”
Section: If and Health Indicators In Laboratory Animalsmentioning
confidence: 99%
“…However, because weight loss may reduce inflammation regardless of the dietary change inducing the weight loss, it will be important to determine if and how eating patterns modify inflammation independently of weight loss. Multiple studies have shown that fasting can lessen symptoms in patients with rheumatoid arthritis (61), and data from animal studies suggest that the pathogenesis of other autoimmune disorders may also be counteracted by IER, including multiple sclerosis (62), lupus erythematosus (63), and type I diabetes (64). In a mouse model of stroke, IER suppressed elevations of TNF and IL-1β in the ischemic cerebral cortex and striatum, which was associated with improved functional outcome (41).…”
Section: Cellular and Molecular Mechanisms: Insight From Intermittentmentioning
confidence: 99%